Loading...

6/y+1=5/y-3 - QuestionCove
OpenStudy (anonymous):

6/y+1=5/y-3

6 years ago
OpenStudy (saifoo.khan):

\[\frac 6y - \frac 5y = -3 -1\]

6 years ago
OpenStudy (anonymous):

? woah, i think u lost me, could u show how u got that?

6 years ago
OpenStudy (saifoo.khan):

lol.

6 years ago
OpenStudy (saifoo.khan):

\[\frac{6-5}{y}= -4\]

6 years ago
OpenStudy (saifoo.khan):

\[y = -\frac{1}{4} \]

6 years ago
OpenStudy (saifoo.khan):

getting it?

6 years ago
OpenStudy (anonymous):

kinda? for me getting math is = to getting rocket science or brain surgery, but thank you for the help :}

6 years ago
OpenStudy (saifoo.khan):

lol, you welcome.

6 years ago
Similar Questions: